Seismological Characterization of the 2021 Yangbi Foreshock‐Mainshock Sequence, Yunnan, China: More than a Triggered Cascade. Issue 8 (26th August 2022) - Zhou, Yijian; Ren, Chunmei; Ghosh, Abhijit; Meng, Haoran; Fang, Lihua; Yue, Han; Zhou, Shiyong; Su, Youjin
Abstract: The 2021 M w 6.1 Yangbi earthquake in southwest China is preceded by three major foreshocks: 05/18 M w 4.3, 05/19 M w 4.6, and 05/21 M w 5.2. It provides a valuable chance to revisit two end‐member foreshock models: cascade‐up and pre‐slip models. We first determine the fault structure with relocated aftershocks and the focal mechanisms obtained from a multipoint‐source inversion. We find that the mainshock and two smaller foreshocks occur on an unmapped near‐vertical fault, and the largest foreshock occurs on a mapped stepover fault that dips to northeast. Second, for each major foreshock, we estimate and delineate the rupture area based on its aftershock location and a spectral ratio analysis. Based on the inferred rupture model, we finally calculate the evolution of Coulomb stress and examine potential interactions between each major event. Results show that the Yangbi sequence can be explained by the cascade triggering mechanism, while we also find evidence for aseismic slip that contributes to the triggering process: the first foreshock is preceded by a short‐term localized cluster, three repeater sequences are detected in the foreshock period, and the aftershock zones expand logarithmically with time. The Yangbi mainshock is probably triggered by multiple major foreshocks through both seismic and aseismic processes. This detailed seismological characterization of Yangbi sequence lends supports for an improved understanding on the foreshock mechanism: (a) the controlling mechanisms are not limited to cascade‐up and pre‐slip. Instead, multiple mechanisms can operate together; and (b) aseismic slip does not always provide more deterministic information on the mainshock. Plain Language Summary: The 2021 magnitude 6.1 Yangbi earthquake in southwest China is preceded by three magnitude 4–5 earthquakes, which are known as foreshocks. Whether the foreshock sequence can be used to forecast future occurrence of large earthquakes is of great scientific interest. Here, we analyze the interaction between these foreshocks with a high‐resolution seismic catalog and the modeling of stress transfer after each major foreshock. We find that the migration directions of foreshocks are not consistent, and that the stress transfer following each foreshock is large enough to explain the triggering of the Yangbi mainshock. This supports the cascade triggering model for foreshock generation, where the foreshocks are not precursors. However, we also find several lines of evidence for aseismic fault slip. These include: the first foreshock is preceded by a short‐term localized cluster, three repeater sequences are detected in the foreshock sequence, and the aftershock zones of three foreshocks expand logarithmically with time, suggesting that they are driven by afterslip. Our results suggest that multiple mechanisms (e.g., cascade‐triggering and aseismic slip) can act at the same time to drive foreshocks, and it is relatively challenging to use foreshocks to forecast future occurrence of large earthquakes. Key Points: The Yangbi mainshock and two smaller foreshocks occur on an unmapped near‐vertical fault, and the largest foreshock occurs on a mapped stepover fault that dips to NE The rupture directivity and source parameters of major foreshocks are estimated by aftershock distribution and spectral ratio analysis The Yangbi sequence can be explained as a cascade sequence, but aseismic processes can also be inferred, including pre‐slip cluster and logarithmic expansion of aftershocks